Voices of creativity and reason in English language teaching - Haase, Christoph (Cognitive linguist) (Cambridge Scholars Publishing, 2021)
This volume underlines the relevance of an empirical, data-based and scientifically informed approach to the teaching of a second or foreign language, even though the contributions gathered here carry out this task through very different means and with various theoretical underpinnings. This is evident especially in the different and versatile perspectives on academic issues in the linguistic and methodological sections of the volume. The contributions here are assembled according to their disciplinary categories of linguistics, methodology of teaching English, and cultural and literary studies.